Hubungan Tingkat Pengetahuan dan Sikap Ibu tentang Gizi Seimbang terhadap Kenaikan Berat Badan pada Balita - Yuyun Triwisnanti (Pusat Riset dan Inovasi Nasional, 2025)
The nutritional status of toddlers is influenced by various factors, including maternal knowledge and attitudes regarding balanced nutrition. As the primary caregiver, the mother plays a vital role in providing food that aligns with the child's growth and developmental needs. This study aims to analyze the relationship between mothers' level of knowledge and attitudes toward balanced nutrition and the weight gain of toddlers, as well as to compare the differences between control and intervention groups. The study employed a quantitative design with a comparative approach involving two groups: control and intervention. The sample consisted of 40 respondents selected through total sampling. Data were collected using a structured questionnaire and analyzed using the Mann-Whitney U test to determine significant differences between the two independent groups. The results revealed a significant difference between the intervention and control groups in terms of maternal knowledge and attitude scores (p = 0.019). The intervention group demonstrated better levels of knowledge and more positive attitudes, which were associated with more optimal toddler weight gain. There is a relationship between maternal knowledge and attitudes toward balanced nutrition and toddler weight gain. Nutrition education interventions have proven to be effective in increasing knowledge and fostering positive maternal attitudes, making them a viable strategy for improving children's nutritional status.